Massimo Campanini. Averroes, the "Decisive Treatise". The Connection Between Islamic Religious Law and Philosophy. Edited with and Introduction by -. Gorgias Islamic Studies 7. Gorgias Press, 2017. ISBN 978-1-4632-0638-3. - Puig Montada, Josep (Anaquel de Estudios Árabes, 2019)
REseña